Dampak Covid-19 Terhadap Perekonomian Indonesia Dari Sisi Pendapatan Nasional Pendekatan Pengeluaran - Ilham Tri Murdo; Junaidi Affan (HOME, 2020)
This study aims to determine the extent of the impact of Covid-19 on the Indonesian economy in terms of national income, which is calculated based on the expenditure method with components of household consumption, gross investment, expenditure and net exports, and future predictions, if the Covid-19 pandemic will continue in the future. long time. From the expenditure side, economic growth in quarter II-2020 compared to quarter II-2019 (y-on-y) contracted in all components. The deepest contraction occurred in the Export of Goods and Services Component of 11.66 percent, followed by the Gross Fixed Capital Formation Component with a contraction of 8.61 percent. The growth in the component of the LNPRT Consumption Expenditure contracted by 7.76 percent, and the growth in the Government Consumption Expenditure component contracted by 6.90 percent. When compared with the previous quarter (q-to-q), economic growth from the expenditure side contracted in all components except for the Government Consumption Component, which grew by 22.32 percent. This is due to an increase in spending on social assistance, especially for the response to the Covid-19 pandemic. The component that experienced the deepest contraction occurred in exports of goods and services amounting to 12.81 percent. Meanwhile, imports of goods and services as a subtracting component decreased by 14.16 percent.